KONTRIBUSI PENDAPATAN PETANI PADI SEBAGAI TENAGA KERJA DI PERKEBUNAN KELAPA SAWIT PT SURYA CIPTA KHURIPAN TERHADAP PENDAPATAN PETANI PADI DI DESA GALI SARI P11 KARANG AGUNG TENGAH KECAMATAN LALAN KABUPATEN MUSI BANYUASIN - Anggara, Tory; Iskandar, Sutarmo (Universitas Muhammadiyah Palembang, 2015)
The Contribution of rice plant farmer income as a labor in oil palm plantation at PT. Surya Cipta Khuripan to the income of rice plant Farmer in Galih Sari P11 Karang Agung Tengah Village, Lalan District, and Musi Banyuasin Regency. This research were to know the income of rice plant farmer as a labor in oil palm plantation at PT. Surya Cipta Khuripan in Galih Sari P11 Karang Agung Tengah Village, Lalan Districtsand Musi Banyuasin Regency and to know income contribution of rice plant farmer as a labor in oil palmplantation at PT. Surya Cipta Khuripan in Galih Sari P11 Karang Agung Tengah Village, Lalan District and Musi Banyuasin Regency. This research was in Galih Sari P11 Karang Agung Tengah Village, in Lalan District, and Musi Banyuasin Regency from June to August 2015. And the Metode of this research was survey metode. And the method of this research was Simple random sampling with the sample were 23 farmer from 76 farmer. The data were collected by interview and observation. While the metode for processing of the data was the metode deskriptif with quantitative approach. The result of the data analysis showed that average of income rice plant as a labor in oil palm plantation at PT. Surya Cipta Khuripan is equal Rp 7.570.956,52 per four months. And The biggest income contribution rice plant farmer as a labor in oil palm plantation at PT. Surya Cipta Khuripan is equal to 32,12 %.